Web content and social media analysis on children's lifestyles even during the Covid-19 pandemic. (20th October 2021) - Nardone, P; Sampaolo, L; Cattaneo, C; Buoncristiano, M; Carletti, CV; Pani, P; Menzano, MT; ,
Abstract: Background: One of the main aims of the project 'Peer education as a tool to reach and involve families and schools in the promotion of healthy lifestyles of children' - funded by the Italian Ministry of Health - is the web & social media (SM) content analysis relating to children's eating habits, physical activity and sedentary behaviours. By discovering which influencers deal with health topics, when, how, and through which channels they do it, countermeasures can be planned, if needed, foreseeing better users' health literacy. This 'web and social listening' and its analysis are even more relevant now at the pandemic, as the parents' use of the web and SM has increased. Methods: Four areas of interest were selected: nutrition, physical activity, sedentary lifestyle and overweight. For each, keywords were defined to search for relevant content (mention). The data were collected between May and December 2020. Results: The mentions collected were 38.146. Of these, 29.666 were used to contruct the panel of 3.100 citations subjected to qualitative analysis. The main Preliminary Results: - Source type: social media 48%, web 52%. 45% of SM content were from Twitter, Instagram (40%), Facebook (14%) and YouTube (0.3%). Facebook accounts had the largest audience Audience profile: 62% women and 38% men; 51% of these were 45-54 and 30% 35-44 years old The most relevant words were: physical activity, children, children's snack, correct nutrition References to the topic 'COVID-19' in the mentions collected concerned 14% of the analysed content The main organisations, by volume of citations, were: World Health Organisation (12%); National Institute of Health (6%); Italian Food Union (6%); Istat (5.5%); Doxa (5%); OKkio alla Salute (5%); Ministry of Health (4%); Coldiretti (4%); UNICEF (3%). Conclusions: The results will contribute to producing indications for health promotion and increasing Internet users' health literacy. Key messages: Women are the main users of the topics investigated. Children and adolescents' health was the central theme in the mentions collected relating to Covid-19.